Rights-based approaches and Indigenous peoples and local communities: Findings from a literature review - Sarmiento Barletti, J.P.; Prouchet, L.; Larson, A.M. (CAB International, 2023)
This preliminary assessment of rights-based approaches (RBAs) seeks to contribute to the ongoing discussions of RBAs for Indigenous Peoples and local communities (IPs and LCs). RBAs purposefully position the recognition of, respect for, and access to individual and collective rights as central to an initiative’s planning, design, implementation, process monitoring, and outcomes. In mainstream climate change, conservation, and development programs and policies, this means refocusing the relationship between “beneficiaries” and “implementers” to one of rights-holders and duty-bearers. RBAs hold growing discursive importance in relation to the rights of IPs and LCs in conservation and climate change spheres, including the agendas of international agencies. The growing interest in RBAs, and their inclusion in frameworks that will guide development, conservation, and climate projects over the next decade, is laudable. However, there are few reviews that seek to understand how RBAs emerged and how they have been conceptualized. Such analysis is a necessary basis from which to advance discussions on the impact of RBAs and provide lessons to support them. In this review, our primary interest is the conception, conceptualization, and implementation of RBAs in forest-based initiatives, but we reviewed the wider scholarly and gray literature on RBAs in development, conservation, and climate action initiatives.